2019
DOI: 10.3389/fpls.2019.00504
|View full text |Cite
|
Sign up to set email alerts
|

Differential Dynamic Changes of Reduced Trait Model for Analyzing the Plastic Response to Drought Phases: A Case Study in Spring Wheat

Abstract: Current limited water availability due to climate changes results in severe drought stress and desiccation in plants. Phenotyping drought tolerance remains challenging. In particular, our knowledge about the discriminating power of traits for capturing a plastic phenotype in high-throughput settings is scant. The study is designed to investigate the differential performance and broad-sense heritability of a battery set of morphological, physiological, and cellular traits to understand the adaptive phenotypic r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
23
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(24 citation statements)
references
References 97 publications
(122 reference statements)
1
23
0
Order By: Relevance
“…Akin biomass, tipping time was affected by seasonal differences (see Supplementary Material ). Vegetative drought stress can delay flowering as reported for wheat (Sanad et al, 2019) and rice (Kondhia et al, 2015; Haque et al, 2016). Early biomass was negatively correlated with tipping, but with progressing growth and development, the signs changed ( Supplementary Figures S15 and S16 ), only disrupted by the wilting of plants.…”
Section: Discussionmentioning
confidence: 82%
See 1 more Smart Citation
“…Akin biomass, tipping time was affected by seasonal differences (see Supplementary Material ). Vegetative drought stress can delay flowering as reported for wheat (Sanad et al, 2019) and rice (Kondhia et al, 2015; Haque et al, 2016). Early biomass was negatively correlated with tipping, but with progressing growth and development, the signs changed ( Supplementary Figures S15 and S16 ), only disrupted by the wilting of plants.…”
Section: Discussionmentioning
confidence: 82%
“…Plant recovery is so far a mainly unexplored trait. However, a recent study in wheat showed that the ability to recover might be useful for selecting drought tolerant genotypes as visually scored plant recovery was correlated with grain yield under a vegetative drought set up in 16 diverse genotypes (Sanad et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…The literature indicates that the consequences of moisture deficit are the most drastic for stress applied at generative phases [ 49 ] and that late stress causes more effects on phenotype than stress at the three-leaf stage [ 18 , 50 ]. The analyzed varieties already exhibited sensitivity to water deficiency at the early developmental stage in our study.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, H 2 O 2 content in leaves correlated negatively with yield. We also found a negative correlation between ROS content in leaves and yield under drought in wheat varieties (Sanad et al ., ). Together, these observations support the idea that ROS accumulation in leaves can be used as an indicator of drought‐susceptibility.…”
Section: Discussionmentioning
confidence: 97%
“…Abiotic stresses including drought, soil salinity, high light intensity and heavy metals are known to increase peroxisome abundance in Arabidopsis (Desai and Hu, ; Sinclair et al ., ; Rodríguez‐Serrano et al ., ; Fahy et al ., ), and drought increases peroxisome abundance in wheat (Sanad et al ., ). Peroxisomes were proposed as a cellular proxy of drought and stresses that induce ROS production (Smertenko, ).…”
Section: Introductionmentioning
confidence: 97%